Ecological stress and individual differences in coping stress on persons permanent limits personal freedom - Terelak, Jan F.; Steckiewicz, Małgorzata (Studia Ecologiae et Bioethicae, 2007)
The paper is empirical in character and concerns people’s individual conditions of dealing with ecological stress involving permanent limits personal freedom. According to literature data, it is assumed the one should expect relatively stable individual differences in dealing with so defined extreme ecological stress. Different styles of dealing with stress in certain situations for a human are pointed out as well as their individual conditions, which can be useful in the creation of a personality conception of social support in the procesess of coping stress and resocialisation.